Rewire your brain think your way to a better life - Arden, John Boghosian (Hoboken, N.J Wiley, 2010)
"Rewire Your Brain focuses on the self-help applications and the ongoing research on the aging brain. Rewire Your Brain is also filled with practical suggestions and exercises to help the reader improve his or her memory and relationships--and overcome mild depression, anxiety issues, procrastination, and various other negative thought patterns. Each of the chapters in this book offer key components of the new developments in neuroscience and describe how to apply them to specific areas of one's life. Rewire Your Brain is a practical book based on well researched principles that work. This book is not for people suffering from severe types of psychological problems, but rather for people facing everyday anxiety, stress, and mild depression. Readers will learn how to minimize those conditions and get the most out of life."--Provided by publisher
Includes bibliographical references (p. 207-229) and index
1
Keywords: Brain; Memory; Neurosciences